Antifungal effect of cumin essential oil alone and in combination with antifungal drugs - SAHADEO PATIL; PANKAJ MAKNIKAR; SUSHILKUMAR WANKHADE; CHANDRAKIRAN UKESH; MAHENDRA RAI (Smujo International, 2015)
Abstract. Patil S, Maknikar P, Wankhade S, Ukesh C, Rai M. 2015. Antifungal effect of cumin essential oil alone and in combination with antifungal drugs. Nusantara Bioscience 7: 55-59. We report evaluation of antifungal activity of cumin seed oil and its pharmacological interactions when used in combination with some of the widely used conventional antifungal drugs using CLSI broth microdilution, agar disc diffusion and checkerboard microtitre assay against Candida. The essential oil was obtained from cumin seeds using hydrodistillation technique and was later evaluated for the presence of major chemical constituents present in it using gas chromatography and mass spectrometry (GC-MS) assay. The GC-MS assay revealed the abundance of ?-terpinene (35.42%) followed by p-cymene (30.72%). The agar disc diffusion assay demonstrated highly potent antifungal effect against Candida species. Moreover, the combination of cumin essential oil (CEO) with conventional antifungal drugs was found to reduce the individual MIC of antifungal drug suggesting the occurrence of synergistic interactions. Therefore, the therapy involving combinations of CEO and conventional antifungal drugs can be used for reducing the toxicity induced by antifungal drugs and at the same time enhancing their antifungal efficacy in controlling the infections caused due to Candida species.